Peran Penyuluh Pertanian Lapangan (PPL) dalam Memengaruhi Keberhasilan Program Pekarangan Pangan Lestari (P2L) di Kecamatan Ajibarang Kabupaten Banyumas - Audira, Daynishelma; Sunendar, Sunendar; Sukmaya, Syahrul Ganda (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
Ajibarang District has implemented “Pekarangan Pangan Lestari” Program (P2L) by empowering women farmer groups (KWT) in the villages. However, these women farmers face limitations in knowledge and skills, necessitating the role of field agricultural extension workers (PPL). Field conditions reveal that one extension worker is responsible for three villages, leading to less effective support. Additionally, there are issues concerning the KWT management in sustaining the program. The aim of this research is to determine the level of PPL's role and the success of the P2L program, identify the factors affecting the success of the P2L program, and assess the impact of PPL's role on the success of the P2L program. The research was conducted in the villages of Tiparkidul, Darmakradenan, and Banjarsari in Ajibarang District, Banyumas Regency. Data collection used total sampling or census, involving 69 women farmers who have benefited from the P2L program. Data analysis methods included validity testing, reliability testing, scoring analysis, and multiple linear regression analysis. The results indicate that internal factors affecting the success of the P2L program among women farmers include education level, yard area, and farming duration. Age does not have a significant impact on the success of the P2L program. The role of PPL emerges as a significant external factor influencing the success of the P2L program in Ajibarang District.